Crònica legislativa del País Basc. Segon semestre de 2020 - Urrutia Libarona, Iñigo; Urrutia Pujana, Leixuri (Revista de llengua i dret, 2021)
"Ús social i altres aspectes institucionals de l'euskera" El treball recull les novetats jurisprudencials i normatives relatives al règim jurídic d'ús de l'euskera al País Basc, produïdes el segon semestre del 2020. "Social use and other institutional aspects of Basque" The article collects the latest case-law and normative developments regarding the legal regime for the use of Basque in the Basque Country, which took place in the second half of 2020. "Uso social y otros aspectos institucionales del euskera"El trabajo recoge las novedades jurisprudenciales y normativas relativas al régimen jurídico de uso del euskera en Euskadi, producidas en el segundo semestre de 2020.